1997
DOI: 10.1021/bi971444j
|View full text |Cite
|
Sign up to set email alerts
|

A Thymocyte Factor SATB1 Suppresses Transcription of Stably Integrated Matrix-Attachment Region-Linked Reporter Genes

Abstract: SATB1 specifically recognizes and binds to specialized genomic regions with an ATC sequence context with high base-unpairing propensity. Such base-unpairing regions (BURs) are typically identified within nuclear scaffold- or matrix-attachment regions (S/MARs). SATB1 is a homeodomain protein and is predominantly expressed in thymocytes. We obtained BHK cell lines expressing low levels of SATB1 by stable transfection and investigated its effect on stably integrated MAR-linked SV40 enhancer/promoter-driven lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 33 publications
4
61
0
Order By: Relevance
“…The highly conserved PU.1-regulating URE is located 16 kb (human) and 14 kb (murine), upstream of the transcriptional start site of PU.1, suggesting that SATB1 has a similar long-range mechanism in myeloid cells. Several reports have shown a transcription-repressing function of SATB1 in T cells (26,27). Recently, Wen et al have shown that SATB1 positively regulates e-globin gene expression in erythroid progenitor cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved PU.1-regulating URE is located 16 kb (human) and 14 kb (murine), upstream of the transcriptional start site of PU.1, suggesting that SATB1 has a similar long-range mechanism in myeloid cells. Several reports have shown a transcription-repressing function of SATB1 in T cells (26,27). Recently, Wen et al have shown that SATB1 positively regulates e-globin gene expression in erythroid progenitor cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…SATB1 is a more T cell-specific protein; Bright being specific for B cells whereas Cux exhibits ubiquitous expression. Cux and SATB1 have been known to function as strong transcriptional repressors (30,31) whereas Bright functions as a transcriptional activator (44). Both Cux and SATB1 proteins play significant role in various processes such as chromatin remodeling, tissuespecific gene regulation, and cell cycle progression, specifying cell fates during cell development and differentiation as well as tumor-specific metabolism (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…MARs help the cell type-specific expression of genes by residing close to enhancers as well as by synergistically acting with them (29), thus maintaining some chromatin domains in condensed inactive structures and others in decondensed transcriptionally active structures. MARs flanking the enhancers in the immunoglobulin or T cell receptor genes are known to function in association with their specific MAR-binding proteins such as Cux (30) and SATB1 (31). Earlier, we reported a novel MAR-binding protein, SMAR1, interacting with MAR␤ (32), a MAR flanking 5Ј-end of the TCR␤ enhancer (E␤) (33).…”
mentioning
confidence: 99%
“…SATB1 regulates transcription activity and recruits chromatin-remodeling factors for region-specific histone modification [12][13][14][15][16], SATB2 activates gamma-globin genes by binding to MARs in their promoters and recruiting histone acetylase PCAF [17]. SAF-B suppresses transcription activity through a recombinant promoter constructs resembling the lysozyme 5` MAR promoter [18].…”
Section: Discussionmentioning
confidence: 99%